Optimization on turmeric extraction to obtain curcuminoid with low-cost operation technique - Abil Fadila; Efri Mardawati; Desy Nurliasari; Roni Kastaman; Selly Harnesa Putri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Turmeric (Curcuma longa L.) has become one of the potential plants to be developed due to its numerous benefits from the active ingredient, curcuminoid. Curcuminoid has antibacterial, antioxidant, and antihepatotoxic properties that can enhance the absorption of vitamins A, D, E, and K. The process to obtain curcuminoid can be carried out through an extraction process using a solvent. This research aimed to optimize the extraction process of curcuminoid from turmeric at a lower cost. The response surface methodology with a central composite design was used in this study to optimize the concentration of ethanol solvent (50-90%, v/v) and the flow rate of ethanol solvent (20-40 mL/minute) on the yield and curcuminoid. The research results indicate that the optimum conditions for the percolation extraction process (ethanol concentration = 90% and ethanol flow rate = 20 mL/minute) result in a yield value of 22.75% (w/w) and curcuminoid content of 13.54% (w/v). The curcuminoid was characterized based on several parameters, including water content of 11.15% (w/w) and antioxidant activity of 98.39% (w/v). The research concludes that the optimum results of the process conditions demonstrate the percolation extraction method with the variables of ethanol concentration and minimal ethanol solvent flow rate, which require lower costs while yielding optimum yield and curcuminoid content. Therefore, this can be applied in further research on curcumin production or its application in the food and non-food industries.